Transcriptome-wide association study of breast cancer risk by estrogen-receptor status - Feng, Helian; Gusev, Alexander; Pasaniuc, Bogdan; Wu, Lang; Long, Jirong; Abu-Full, Zomoroda; Aittomäki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Antoniou, Antonis C.; Arason, Adalgeir; Arndt, Volker; et al. (Genetic epidemiology, 2020)
Previous transcriptome-wide association studies (TWAS) have identified breast cancer risk genes by integrating data from expression quantitative loci and genome-wide association studies (GWAS), but analyses of breast cancer subtype-specific associations have been limited. In this study, we conducted a TWAS using gene expression data from GTEx and summary statistics from the hitherto largest GWAS meta-analysis conducted for breast cancer overall, and by estrogen receptor subtypes (ER+ and ER-). We further compared associations with ER+ and ER- subtypes, using a case-only TWAS approach. We also conducted multigene conditional analyses in regions with multiple TWAS associations. Two genes, STXBP4 and HIST2H2BA, were specifically associated with ER+ but not with ER- breast cancer. We further identified 30 TWAS-significant genes associated with overall breast cancer risk, including four that were not identified in previous studies. Conditional analyses identified single independent breast-cancer gene in three of six regions harboring multiple TWAS-significant genes. Our study provides new information on breast cancer genetics and biology, particularly about genomic differences between ER+ and ER- breast cancer.